(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hospital readmissions among patients with chronic diseases pose a persistent challenge to healthcare systems, particularly in low- and middle-income countries where continuity of care is often fragmented. Nurse-led telehealth follow-ups have emerged as a viable strategy to strengthen transitional care, enhance patient self-management, and reduce avoidable readmissions. This quasi-experimental study evaluated the effectiveness of structured nurse-led telehealth follow-ups in preventing 30-day hospital readmissions among patients with chronic diseases discharged from Nishtar Hospital, Multan. A total of 780 patients were enrolled and allocated into a telehealth intervention group (n = 385) and a usual care group (n = 395). Primary outcomes included 30-day all-cause readmission rates, while secondary outcomes assessed emergency department visits, medication adherence, self-management confidence, and patient satisfaction. Results demonstrated a statistically significant reduction in readmission rates in the telehealth group compared to usual care (10.9% vs. 20.0%, p < 0.001). Secondary outcomes also showed marked improvements in adherence, self-efficacy, and satisfaction. These findings support the integration of nurse-led telehealth follow-ups into discharge planning and chronic disease management pathways in tertiary care hospitals.